The sensitivity variation of the radiation induced signal in deciduous teeth to be used in ESR tooth enamel dosimetry. (November 2017) - Murahashi, Mika; Toyoda, Shin; Hoshi, Masaharu; Ohtaki, Megu; Endo, Satoru; Tanaka, Kenichi; Yamada, Yudai
Abstract: The sensitivities to dose of the radiation induced signal observed in tooth enamel were examined by electron spin resonance (ESR) for individual deciduous and permanent teeth. The sensitivities in deciduous teeth are in agreement with those in permanent teeth within the statistical error while the variation is larger in deciduous teeth than in permanent teeth. While the intensities of the interfering background signal are also similar, the average value of the line widths of the background signal are larger but statistically indistinguishable due to larger variations in deciduous teeth than in permanent teeth. The position of the background signal (g factor) in deciduous teeth is slightly different from that in permanent teeth. With these similarities and differences, the ESR dosimetry with deciduous teeth will be useful as with permanent teeth using the same experimental procedures. The obtained dose will have larger statistical error in deciduous teeth than in permanent teeth when the calibration line method is applied, as the variation in sensitivity of deciduous teeth is larger. Highlights: ESR signals were examined in individual deciduous tooth enamel samples. The RIS sensitivity of deciduous teeth are similar with that in permanent teeth while its variation is larger. The BGS intensity of deciduous teeth are also similar with that in permanent teeth while its variation is also larger. The average of the line width of BGS in deciduous and permanent teeth are indistinguishable due to variation. The line position (g factors) of BGS in deciduous teeth is at slightly higher field than in permanent teeth. With these similarities and differences, ESR dosimetry with deciduous teeth will be also useful as with permanent teeth.